Evaluating the Impact of Policy and Programming on Female-Victim Intimate Partner Homicide at the County Level in Florida - Montanez, Julio (Violence against women, 2023)
Legal and social service interventions aim to mitigate intimate partner violence (IPV) and keep IPV from becoming lethal. Accordingly, this study examines the impact of policies and programs on female-victim intimate partner homicide (FVIPH) rates across the 67 counties of the state of Florida. It focuses on community coordinated response efforts, batterer intervention programs, local domestic violence (DV) ordinances, DV fatality review teams, and DV shelter programs. Results indicate that community coordinated response efforts are associated with decreasing FVIPH rates. Discussions of findings, limitations, and implications are provided accordingly.